2022
DOI: 10.2337/dc21-1757
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Related Medication Nonadherence in Adults With Diabetes in the United States: The National Health Interview Survey 2013–2018

Abstract: OBJECTIVE Health-related expenditures resulting from diabetes are rising in the U.S. Medication nonadherence is associated with worse health outcomes among adults with diabetes. We sought to examine the extent of reported cost-related medication nonadherence (CRN) in individuals with diabetes in the U.S. RESEARCH DESIGN AND METHODS We studied adults age ≥18 years with self-reported diabetes from the National Health Interview … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 38 publications
5
16
0
Order By: Relevance
“…Moreover, this study also showed that patients with low household incomes were found more likely to be low adherent to their medications compared to patients who had relatively high household income. This finding agrees with previous studies [ 42 , 43 , 48 ], which patients with low economic status and household income have the potential to withdraw medications because of affordability issues. This problem is severe in chronic illnesses and patients with comorbidities because of increased medication costs for treating additional conditions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, this study also showed that patients with low household incomes were found more likely to be low adherent to their medications compared to patients who had relatively high household income. This finding agrees with previous studies [ 42 , 43 , 48 ], which patients with low economic status and household income have the potential to withdraw medications because of affordability issues. This problem is severe in chronic illnesses and patients with comorbidities because of increased medication costs for treating additional conditions.…”
Section: Discussionsupporting
confidence: 93%
“…patients who received their medication freely. This finding agrees with previous studies [42][43][44]. The finding indicates that patients who cover medication costs directly form out of pocket may sustain an increase in mediation costs and be forced to withdraw when the medication cost become expensive.…”
Section: Plos Onesupporting
confidence: 92%
“…Moreover, this study also showed that patients with low household incomes were found more likely to be low adherent to their medications compared to patients who had relatively high household income. This agrees with previous studies (42,43,48), which patients with low economic status and household income have the potential to withdraw medications because of affordability issues. This problem may be severe in chronic illnesses and patients with comorbidities because of increased medication costs.…”
Section: Discussionsupporting
confidence: 93%
“…This study showed that the source of cost coverage of medications was signi cantly associated with levels of medication adherence, which patients who were paid out of pocket for their medication were found more likely to have poor medication adherence compared with patients who received their medication freely. This nding agrees with previous studies (42)(43)(44). The nding indicates that patients who cover medication costs directly form out of pocket may sustain an increase in mediation costs and be forced to withdraw when the medication cost become expensive.…”
Section: Discussionsupporting
confidence: 92%
“…17 Approximately one-third of US adults using insulin report either rationing, dose skipping, or delaying prescription refills to save money. 18 Second, only a small proportion of practitioners may be starting or intensifying insulin therapy in a timely manner. 19 Third, acceptability of insulin remains low among patients, leading to reluctance to begin or continue using insulin therapy as recommended.…”
Section: Discussionmentioning
confidence: 99%